Chinese first-year undergraduates’ strategy use in the English writing from sources task: influences from genders, critical thinking, and L2 proficiency - Liu, Wei; Zhao, Pengfei (Frontiers in Psychology, 2023)
English is widely used as a lingua franca in academic settings, including academic writing, in the modern age. When faced with complex writing tasks that involve multiple sources, the ability to effectively employ writing strategies becomes crucial for achieving writing success. This is particularly true for first-year university students who are learning English as a foreign language. Although previous studies have examined various individual difference factors that influence students' use of source-based writing strategies, such as L2 proficiency and gender, there is a lack of research exploring the impact of critical thinking skills on students' strategy use. To address this gap, the current study utilized a convenience sampling procedure to involve 526 first-year EFL undergraduates from six classes in mainland China. A writing task and questionnaire were employed to investigate the students' critical thinking skills and strategy use during the English writing from sources task. Furthermore, the study examined whether there were differences in strategy use based on gender, L2 proficiency groups, and levels of critical thinking ability. A three-way MANOVA was conducted, revealing significant variations in the students' writing strategy use based on gender, L2 proficiency groups, and critical thinking levels. Notably, interaction effects between critical thinking ability and gender were also observed. The study discusses important implications, emphasizing the need for teachers to integrate critical thinking and strategy training into practical writing classes, and to consider the diverse learning needs of different groups of students.